Análisis de los principales productos importados desde China hacia Ecuador. - Reyno Sanchez, Sixto Xavier (My University, 2021)
At present, faced with the health crisis that the world is going through due to the COVID-19 Pandemic, the need arises to look for new sources of income to support the family economy, so sporadic imports of products for commercialization in the markets local is an activity that is increasing. Therefore, the present investigation aims to determine the process and import costs of a batch of Xiaomi Mi Note 10 cell phones from China to Ecuador, through the application of the import regime for consumption for commercialization in the local market. The methodology starts from a descriptive stage and the documentary review through secondary sources is the starting point for the construction of the theoretical framework, in order to give scientific support to the research. The results allow the company to identify the processes, calculate the costs and apply the respective regulations for the import regime, also opening a line for future research where the subject of study is deepened to a greater extent.
En la actualidad, frente a la crisis sanitaria que atraviesa el mundo por la Pandemia del COVID-19, surge la necesidad de buscar nuevas fuentes de ingresos para sustentar la economía familiar, por lo que las importaciones esporádicas de productos para la comercialización en los mercados locales es una actividad que va en aumento. Por lo tanto, la presente investigación tiene como objetivo determinar el proceso y costos de importación de un lote de celulares Xiaomi Mi Note 10 desde China hacia Ecuador, mediante la aplicación del régimen de importación a consumo para la comercialización en el mercado local. La metodología parte desde una etapa descriptiva y la revisión documental a través de fuentes secundarias es el punto de partida para la construcción del marco teórico, con el fin de dar un respaldo científico a la investigación. Los resultados, permiten a la empresa identificar los procesos, calcular los costos y aplicar la respectiva normativa para el régimen de importación, además abre una línea para futuras investigaciones donde se profundice en mayor medida el tema de estudio.
Keywords: IMPORTACIÓN; COSTOS; NORMATIVA; DOCUMENTACIÓN